Distribution of Extreme Vital Signs and Complete Blood Count Values of Healthy Parturients: A Retrospective Database Analysis and Review of the Literature. Issue 2 (June 2020) - Gat, R.; Hadar, E.; Orbach-Zinger, S.; Shochat, T.; Kushnir, S.; Einav, S.
Abstract : ( Anesth Analg . 2019;129:1595–1606) Maternal near-miss events and excess mortality remain problematic throughout the world, and as such, scoring methods intended to identify early maternal deterioration have become a standard of care in many delivery suites and maternity wards. However, all of these rely on predefined ranges of "normal" laboratory values and vital signs (VSs), but the effect of normal physiological adjustments on maternal VSs has yet to be fully established. The objective of this study was to determine the extremes of VS and blood count values in healthy pregnant women in the peripartum time period who had single offspring. It was a retrospective analysis of data collected during real-time deliveries (from July 2012 to June 2016) at a labor and delivery (L&D) ward in Israel.